Chlorogenic Acid Attenuates Bleomycin-Induced Pulmonary Fibrosis in a Murine Model by Modulating TGF-β1 Expression - Juan Manuel Velázquez-Enríquez; Alma Aurora Ramírez-Hernández; Jovito César Santos-Álvarez; Edilburga Reyes-Jiménez; Antonio Arcos-Román; Jaime Arellanes-Robledo; Carlos Alberto Matias-Cervantes; María del Socorro Pina-Canseco; Verónica Rocío Vásquez-Garzón; Rafael Baltiérrez-Hoyos (Advances in Respiratory Medicine, 2026)
Background: Idiopathic pulmonary fibrosis (IPF) is a progressive interstitial lung disease driven by aberrant extracellular matrix deposition, with the activity of transforming growth factor-beta 1 (TGF-β1) orchestrating fibrogenesis. Current therapies are limited by severe adverse effects, highlighting the unmet need for safer treatments. In this study, the therapeutic potential of chlorogenic acid (CGA) in a murine model of pulmonary fibrosis was evaluated. Methods: Pathology was induced on day 0 via subcutaneous osmotic minipumps delivering bleomycin (BLM) for one week, followed by pump removal on day 10. Therapeutic interventions with intragastric CGA (60 mg/kg) were administered daily from days 14 to 20. Lung tissue samples obtained on day 21 were analyzed via histological, immunohistochemical, and RT–PCR methods. Results: Histological analysis via H&E and Masson’s trichrome staining revealed that CGA treatment significantly attenuated alveolar thickening, restored the alveolar space, and reduced the total cell density and Ashcroft fibrosis score. Furthermore, CGA markedly decreased collagen deposition. Quantitative RT–PCR and immunohistochemical assays revealed that CGA effectively decreased the expression of Col1a1, TGF-β1, and the myofibroblast marker alpha-smooth muscle actin (α-SMA). Conclusions: CGA exerts important therapeutic effects by decreasing the expression of TGF-β1 and the activation of myofibroblasts, indicating that this natural polyphenol is a promising candidate for mitigating the progression of pulmonary fibrosis.